A migração haitiana e a inserção no mercado de trabalho na cidade de Cascavel/PR - Manica, Carmem Aparecida (2018)
Natural catastrophes and economical and political problems have been working as catalysts for migration of an extensive amount of the Haitian population to other countries. The migratory route to Brazil has increased after the natural disaster of January 10th 2010, when Haiti was struck by a level 7 earthquake in the Richter scale. According to data from the Brazilian Ministry of Labour and Employment, around 30,000 Haitians have immigrated to the country. Cities such as Manaus/AM, Tabatinga/AM, São Paulo/SP, Curitiba (PR), and Cascavel/PR are some of the destinies chosen by these migrants, accounting that 3,000 Haitians currently live in the latter. The main objective of the present research is to investigate the Haitian migratory activity to Brazil, specifically in the city of Cascavel, state of Paraná, from the year 2010, analyzing their integration in the local workforce, as well as to understand the migrants' perspective on the conditions of such integration. In order to achieve these goals, the methods of bibliographical review and exploratory research were employed. Data collection was achieved through qualitative field research, using participant observation and oral telling.